Using Humor To Navigate The Dynamics of Multiculturalism In Anwar Zahid’s Religious Preachings - Silvia Lubaba; Edi Dwi Riyanto (Syntax Literate, 2022)
Many preachers use jokes or humor in delivering their da'wah (religious preaching). One of the preachers who often use humor in their religious lectures is Anwar Zahid, a well-known traditional preacher from Bojonegoro, East Java. The purpose of this study is to reveal the humor techniques used by Anwar Zahid in his two lectures on Youtube. The analysis is based on Arthur Asa Berger's humor theory. The results showed that Anwar Zahid used several humor techniques in his religious preachings such as Bombast, Catalog, Coincidence, and others. Humor is also an effort to navigate the dynamics and various changes in multiculturalism that occur in society. In addition, the humor serves to release the tension of the audience.